Community advisory boards: Experiences and common practices of clinical and translational science award programs. Issue 5 (20th October 2019) - Stewart, M. Kathryn; Boateng, Beatrice; Joosten, Yvonne; Burshell, Dana; Broughton, Hilary; Calhoun, Karen; Huff Davis, Anna; Hale, Rachel; Spencer, Nicola; Piechowski, Patricia; James, Laura
Abstract: Community advisory boards (CABs) are a valuable strategy for engaging and partnering with communities in research. Eighty-nine percent of Clinical and Translational Science Awardees (CTSA) responding to a 2011 survey reported having a CAB. CTSAs' experiences with CABs are valuable for informing future practice. This study was conducted to describe common CAB implementation practices among CTSAs; document perceived benefits, challenges, and contributions; and examine their progress toward desirable outcomes. A cross-CTSA collaborative team collected survey data from respondents representing academic and/or community members affiliated with CTSAs with CABs. Data representing 44 CTSAs with CABs were analyzed using descriptive statistics. A majority of respondents reported practices reflecting respect for CAB members' expertise and input such as compensation (75%), advisory purview beyond their CTSA's Community Engagement program (88%), and influence over CAB operations. Three-quarters provide members with orientation and training on roles and responsibilities and 89% reported evaluating their CAB. Almost all respondents indicated their CTSA incorporates the feedback of their CABs to some degree; over half do so a lot or completely. This study profiles practices that inform CTSAs implementing a CAB and provide an evaluative benchmark for those with existing CABs.